2021
DOI: 10.3390/nu13072304
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Nutrition and Culinary Education in Response to Food Insecurity in a Public University

Abstract: Food insecurity is an emerging issue for college students. A nutrition course with an integrated teaching kitchen was developed to address this issue at a large public university. We aimed to determine changes in food insecurity and stress among students who took the course. The course consisted of weekly lectures followed by teaching kitchen lab sessions to teach basic nutrition and culinary concepts and expose students to hands-on skill development cooking experiences. Using a pre-post design, enrolled stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The results from our study are unprecedented, as they demonstrate the association of food security to better diet quality, measured in wider context, considering food preparation and consumption. Furthermore, improving the quality of diets using culinary skills to promote cooking self-efficacy and food agency might be a way of reducing food insecurity and perceived stress in university students, as successfully addressed by Matias et al [38]. Thus, programs addressing cooking self-efficacy and food agency might be helpful to our studied population.…”
Section: Discussionmentioning
confidence: 80%
“…The results from our study are unprecedented, as they demonstrate the association of food security to better diet quality, measured in wider context, considering food preparation and consumption. Furthermore, improving the quality of diets using culinary skills to promote cooking self-efficacy and food agency might be a way of reducing food insecurity and perceived stress in university students, as successfully addressed by Matias et al [38]. Thus, programs addressing cooking self-efficacy and food agency might be helpful to our studied population.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, as FI has been related to lower food and financial literacy (16,97,98), interventions that aim to increase these skill sets are crucial. Matias and colleagues demonstrated a semester-long nutrition intervention can decrease FI by 22% (99). While this demonstrates the potential these interventions can have, it is important to note that student needs differ across campuses.…”
Section: Researchmentioning
confidence: 98%
“…For example, improving FI students’ food knowledge and skills can help them make healthier food choices and reduce the risk posed by an unhealthy food environment. A study of 171 undergraduates at a large PHEI enrolled in a nutrition and culinary skills class found that the course significantly decreased FI and stress levels, and that decreased FI was associated with increased vegetable and especially fruit intake [ 67 ] (although the mechanism for this increase was not investigated). FI students themselves have stated their desire for help in learning to cook inexpensive nutritious food [ 68 ].…”
Section: How Do Campus Food Environments Affect Student Food Choice F...mentioning
confidence: 99%